2000
DOI: 10.1177/107327480000700301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Thyroid Nodule

Abstract: Thyroid function tests rarely help a differential diagnosis. Fine-needle aspiration is the "gold standard" for diagnosis. Tiny "incidentalomas" are often followed with repeat monitoring for change of size or character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
1
17
0
8
Order By: Relevance
“…Its use is recommended in patients with suppressed TSH to document whether a nodule is functioning or not. 1,76,102 According to its uptake, a nodule is considered functioning or "hot" (i.e. has tracer uptake greater than the surrounding normal thyroid), isofunctioning or "warm" (i.e.…”
Section: Scintigraphy (Sc)mentioning
confidence: 99%
“…Its use is recommended in patients with suppressed TSH to document whether a nodule is functioning or not. 1,76,102 According to its uptake, a nodule is considered functioning or "hot" (i.e. has tracer uptake greater than the surrounding normal thyroid), isofunctioning or "warm" (i.e.…”
Section: Scintigraphy (Sc)mentioning
confidence: 99%
“…Thyroid nodules are quite common in the general population, though thyroid cancer is relatively uncommon with annual incidence in united states of about 37,340 cases in 2008, which constitute about 2.6% of all cancers and 0.3% of all cancers death. 4 The frequency of malignancy in cold nodule is highly variable; a histopathological review of 400 cases showed 10% to be malignant, 5 while in another study histopathology of 104 solid cold nodules showed 36 (34.6%) to be malignant. 6 The literature is unclear regarding this topic and gives frequency of malignancy in cold thyroid nodule with a very variable range 10% -34.6%.…”
Section: Original Articlementioning
confidence: 99%
“…6 The literature is unclear regarding this topic and gives frequency of malignancy in cold thyroid nodule with a very variable range 10% -34.6%. 5,6 The study is to find the exact frequency of malignancy in our local population and helps for early diagnosis and prompt management of the patient to reduce the morbidity and mortality.…”
Section: Original Articlementioning
confidence: 99%
“…Literatūroje nurodomas įtariamo vėžio citologinės grupės dažnumas yra 10-40 proc. (7)(8)(9)(10). Įtaria-mo vėžio citologinės grupės dažnumas sutampa su literatūroje nurodytais duomenimis, o folikulinių neoplazmų grupėje piktybinių pokyčių dalis yra gerokai didesnė ir sudaro 55,5 proc.…”
Section: Rezultatų Aptarimasunclassified